The role of emergency medical services in the management of in-hospital emergencies: Causes and outcomes of emergency calls - A descriptive retrospective register-based study - Myrskykari Henna; Iirola Timo; Nordquist Hilla (Elsevier Ltd, 2026)
Background
Medical emergency teams (METs) are in place in some hospitals in Finland to respond to critical emergency events. However, in hospitals without dedicated METs, staff are instructed to call emergency medical services (EMS) to deal with emergencies. This study examined the reasons for calling EMS to hospitals and the outcomes of these calls.
Methods
Descriptive retrospective register-based study of the response and management of in-hospital emergencies by EMS in the wellbeing services county of Southwest Finland. Patient care reports of the EMS and those of the hospitals were analysed.
Results
In total, 138 medical emergencies managed by EMS were included in this study. 108 of these related to patients, and 25 related to hospital personnel. Cardiac arrest (n = 36) and a reduced level of consciousness (n = 29) were the most common in-hospital emergencies. In 68% of in-hospital emergencies managed by the EMS team, after calling 112, hospital personnel implemented various treatment measures. In 72% of cases, follow-up treatment was required.
Conclusions
Hospital personnel are able to initiate medical measures in emergencies, even when no MET is available. Although EMS are important in responding to in-hospital emergencies, they seem to be performing the same role as METs.